Transit Challenges in Mozambique in the context of Trade Facilitation Practical solutions - Cintura, Herculano (ALBA - ISFIC Research and Science Journal, 2026)
This reflection aims at discussing the main transit challenges affecting Mozambique, in the context of trade facilitation measures implementation, and proposing practical solution to help overcome these obstacles. Coordination has been identified as the key factor in addressing transit obstacles. Key words: Coordination, Customs, Transit and Trade Facilitation